The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1177/1457496914553149
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss prior to bariatric surgery: An updated review of the literature

Abstract: Background and Aims: prior to bariatric surgery, a preoperative weight-reducing regimen is usually adhered to in most centers. the clinical effects of such a regimen are yet to be determined.Material and Methods: We reviewed the current literature by searching in pubMed for publications reporting clinical effects resulting from a preoperative weight loss regimen prior to bariatric surgery published from January 1, 1995 to april 30, 2014.Results: in total, we identified 23 original publications and 2 review art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 37 publications
0
73
0
7
Order By: Relevance
“…It is not clear in the published literature that the weight loss prior to bariatric surgery has any impact on surgical morbidity (10,13,16,18). In fact, the influence of pre-surgical weight on surgical morbidity is also uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not clear in the published literature that the weight loss prior to bariatric surgery has any impact on surgical morbidity (10,13,16,18). In fact, the influence of pre-surgical weight on surgical morbidity is also uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…However, other retrospective studies have found that a pre-surgical weight loss of 5-10% EWL will have an impact on post-surgical morbidity (9,10,16,20), on the time duration of the surgery (19), on the amount of transfusions, and on the rate of conversions to open surgery (6,21,22). Other authors have found that pre-surgical weight loss is a predictive factor for a higher loss weight during post-surgical evolution (6,17), and would help to select those obese population who would benefit most from bariatric surgery.…”
Section: Obesity (Bmi ≥ 30 Kg/mmentioning
confidence: 99%
See 1 more Smart Citation
“…This is usually achieved with Low Calorie Diets (LCD) or Very Low Calorie Diets (VLCD), where the patient wholly or partly subsists on meal replacements such as shakes, soups and puddings which provide 600-800 kcal/day [12]. A systematic review and meta-analysis has shown that preoperative weight loss results in shorter operating times and improved weight loss a year after surgery [13].…”
Section: Introductionmentioning
confidence: 99%
“…Alguns estudos demostraram que a perda de peso em indivíduos com obesidade mórbida antes da cirurgia bariátrica promoveu controle das comorbidades, redução do risco cirúrgico, de infecções e de mortalidade, e aumento a adesão do paciente no período pós-operatório 15,16,17,18 .…”
Section: Perda De Peso No Período Pré-operatório De Cirurgia Bariátricaunclassified